Usability Analysis of The Student Service Information System at The Faculty of Engineering Tadulako University Using Heuristic Evolution and The System Usability Scale (SUS) - Noviantika, Noviantika; Syahrullah, Syahrullah; Laila, Rahma; Lapatta, Nouval Trezandy; Wirdayanti, Wirdayanti (Universitas Raharja, 2025)
The Student Service Information System is defined as a system designed to assist students, faculty, and administration at Tadulako University's Faculty of Engineering in managing various academic aspects. This research identifies issues or obstacles users face while utilizing the website. The usability evaluation employs the Heuristic Evaluation method and the System Usability Scale (SUS). Based on the research conducted with 100 respondents, all active students at Tadulako University, the usability measurements revealed significant findings. According to the Heuristic Evaluation method, which utilizes 10 principles, areas requiring improvement were identified in qualifications B1.2, B3.3, B8.2, B10.2, and B10.3. Recommendations for enhancements include adding a notification feature, ensuring the search function is easily discoverable, selecting appropriate color combinations, and improving the placement of the user guide. The System Usability Scale yielded a score of 50, categorizing the website as